cGAS/STING and innate brain inflammation following acute high-fat feeding - Sarah E. Elzinga; Sarah E. Elzinga; Rosemary Henn; Rosemary Henn; Benjamin J. Murdock; Benjamin J. Murdock; Bhumsoo Kim; Bhumsoo Kim; John M. Hayes; John M. Hayes; Faye Mendelson; Faye Mendelson; et al. (Frontiers in Immunology, 2022)
Obesity, prediabetes, and diabetes are growing in prevalence worldwide. These metabolic disorders are associated with neurodegenerative diseases, particularly Alzheimer’s disease and Alzheimer’s disease related dementias. Innate inflammatory signaling plays a critical role in this association, potentially via the early activation of the cGAS/STING pathway. To determine acute systemic metabolic and inflammatory responses and corresponding changes in the brain, we used a high fat diet fed obese mouse model of prediabetes and cognitive impairment. We observed acute systemic changes in metabolic and inflammatory responses, with impaired glucose tolerance, insulin resistance, and alterations in peripheral immune cell populations. Central inflammatory changes included microglial activation in a pro-inflammatory environment with cGAS/STING activation. Blocking gap junctions in neuron-microglial co-cultures significantly decreased cGAS/STING activation. Collectively these studies suggest a role for early activation of the innate immune system both peripherally and centrally with potential inflammatory crosstalk between neurons and glia.